Effect of tree forage supplementation on growth performance of goats - Rahman, Md Zillur; Akbar, Md Ali; Hossain, Md Abul; Ali, Md Yousuf (Asian Journal of Medical and Biological Research, 2015)
An experiment with 25 growing goats (in 5 groups) were fed four different tree forage based diets (B,C,D,E) and control A showed that there were significant (p<0.05) differences in DM , ME and DCP intakes. Although there were no significant differences in the digestibility of DM, OM, CP and ADF but intake of these nutrients were significantly (p<0.05) differed among the treatments. There were no significant differences in the digestibility of diets having different forages but they were significantly higher than that of grass based control diet. Feeding of tree forages had significant (p<0.05) effect on live weight gain of goats. Animals fed tree forage based diets significantly (p<0.05) increased weight gain (60.03, 59.10, 57.75 and 55.57 g/d for Sesbania grandiflora, Leucaena leucocephala, Erythrina orientalis and Morus alba, respectively) compared to that of control group (39.25 g/d) . However, there were no significant differences in weight gain of the animals fed different tree forage based diets. Feed conversion efficiency (kg feed/kg gain) also showed that animals fed tree forage based diets presented significantly (p<0.01) higher efficiency (11.74, 12.05, 12.21 and 12.02) for L. leucocephala, E. orientalis, S. grandiflora and M. alba compared to that (16.00) of fed control diet. Nitrogen balance trial showed that there were significant (p<0.05) differences among the mean values in terms of total N intake (g/d), nitrogen retention (%) and nitrogen balance (g/d). It may be concluded that supplementation of diets with tree forages resulted in better weight gain, digestibility and nitrogen balance compared to green grass. So, the diets of goats may be supplemented with tree forages of S. grandiflora, L. leucocephala, E. orientalis and M. alba for improved growth performance. Asian J. Med. Biol. Res. June 2015, 1(2): 209-215